Investigation of Conical Spinneret in Generating More Dense and Compact Electrospun Nanofibers - Aya Hamed (Polymers, 2017)
Electrospinning is an important, widely used process to generate nanofibers. However, there is still an open window for different designs of both spinneret and collector electrodes to be investigated. This paper introduces the impact of new design of conical spinneret electrode on the generated electrospun nanofibers. In this work, the conical feeder is used to generate electrospun Poly(vinyl alcohol) (PVA) nanofibers, and being compared to the traditional needle feeder at the same processing conditions. The jet’s mechanism is simulated using discrete bead model along with estimated calculations of both deposition area and fiber radius. The electric field distribution that is around the charged cone is analyzed. Based on both theoretical modeling and experimental measurements, a comparison of mean diameter, deposited area, and the thickness of generated nanofibers is presented related to both conical and needle electrodes. Conical feeder shows clearly compact nanofibers mat in terms of deposition area (spherical deposition of diameter ~6 cm) up to half-area of needle deposited nanofibers with high fiber density for the same time of the process. Moreover, the conical electrode is found to have privilege in terms of productivity rate and operation time. This study can be useful in generating localized nanofibers within different applications, such as biomedical tissue scaffolds, textile, and sensors.